Pengaruh Informativeness, Entertainment, dan Kredibilitas Iklan terhadap Sikap Audience atas Iklan Nokia di Web - Astuti, Sri Wahjuni; Wiharsa, Karina (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2005)
Advertisement function is informative, persuasive, and remind. Referring to these functions and its role, nature of informativeness (ability inform), believable (credible) and something that facilitates people to remember, for example by giving entertainment amusement for audiences, representing determinant in develop; building attitude such as like the (Positive) or do not like the (negative) somebody at the advertisement. This research conducted at advertisement Nokia in web (internet) with the responder of students of Airlangga University visiting minimum sites web cell phone Nokia ones. This research proves that assessment of student of Airlangga University for informativeness, entertaint and credibility of an advertisement have an effect on the attitude of Student of Airlangga University for adVertisement Nokia in web.